The Impact of Work-Life Balance and Work-Family Conflict on Job Satisfaction: The Mediating Role of Emotional Exhaustion - Anggi Putri Septiani; Purwanto, Edy (Universitas Muhammadiyah Pontianak, 2026)
This quantitative study examined how work-life balance, work-family conflict, and emotional exhaustion relate to job satisfaction among 102 Generation Z female employees in Semarang using SmartPLS. Work-life balance improved job satisfaction, whereas work-family conflict unexpectedly showed a positive direct association with it. Work-family conflict raised emotional exhaustion, while work-life balance had no significant influence on it. Emotional exhaustion lowered job satisfaction. Mediation testing showed that emotional exhaustion did not transmit the effect of work-life balance, but fully transmitted the effect of work-family conflict, on job satisfaction.